2014
DOI: 10.1016/j.psychres.2013.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a best-possible-self mental imagery exercise on mood and dysfunctional attitudes

Abstract: a b s t r a c tDispositional optimism has been related to positive physical and mental health outcomes, increased positive mood ratings and cognitions about the future. In order to determine the causal relation between optimism and mood and cognitions optimism should be manipulated experimentally. The current study tested the effects of a best-possible-self mental imagery exercise on affect and mood ratings and dysfunctional cognitions following a sad mood induction in undergraduate students (N ¼40). Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 22 publications
2
53
1
3
Order By: Relevance
“…An earlier study of our group showed that positive mental imagery of the future is associated with higher levels of optimism (Blackwell et al, 2013). A recent study showed that the use of a mental imagery exercise, called the Best-Possible-Self exercise, can reinstate positive affect and cognitions after sad mood induction (Renner et al, 2014). Despite that this experiment had only been conducted among healthy participants, it opens a new venue for treatment and prevention of affective disorders.…”
Section: Discussionmentioning
confidence: 92%
“…An earlier study of our group showed that positive mental imagery of the future is associated with higher levels of optimism (Blackwell et al, 2013). A recent study showed that the use of a mental imagery exercise, called the Best-Possible-Self exercise, can reinstate positive affect and cognitions after sad mood induction (Renner et al, 2014). Despite that this experiment had only been conducted among healthy participants, it opens a new venue for treatment and prevention of affective disorders.…”
Section: Discussionmentioning
confidence: 92%
“…These results are in line with the findings of Pietrowsky and Mikutta [72], who showed that, after practicing the BPS, depressive patients decreased their BDI levels. Unlike previous BPS studies that did not find any interaction effect of induced optimism on negative affect, compared to a control condition [38,39,69,73], we found a significant effect on negative affect. Moreover, these changes were maintained at the follow-ups.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is consistent with the study by Pennebaker (1993), who showed that, independently of the emotional content of the writing, enhancing the use of words that express awareness or are related to cognitive activity was linked to improvements in health. Furthermore, other studies also showed that the daily activities exercise was able to improve dysfunctional attitude levels (Renner, Schwarz, Peters & Huibers, 2014) and diminish negative affect (Sheldon & Lyubomirsky, 2006). For this reason, it would be interesting to choose another more innocuous control activity in order to test the effects in a fairer way.…”
Section: Discussionmentioning
confidence: 99%